Financialization x Gamblification: Key Concepts for the Critique of Cryptocurrency Exchanges - French, Martin; Swiffen, Amy; Bélanger, Raphaël; Fiedler, Ingo; Bordeleau, Erik; Hurl, Chris; Hoebanx, Pauline; Chugh, Neha; Hastings, Colin; Jourdenais, Pierre-Olivier; Kairouz, Sylvia; Lajeunesse, Marc; et al. (Critical Gambling Studies)

(untitled) (University of Alberta Library, 2024)
The blurring of gambling and crypto-finance reflects a wider set of complex social transformations. To help parse these transformations, we discuss two key concepts: financialization and gamblification. On their own, these concepts are useful—if insufficient—for the critical theorization of cryptocurrency exchanges. Taken together, they help highlight the deep interrelationship of cryptocurrency exchanges and gambling in our contemporary moment. Reflecting on the example of BitMEX, a centralized cryptocurrency exchange notable for its gamified interface, we argue that cryptocurrency discourse may operate to obscure the structural mechanisms that transfer wealth from users to platform operators while further embedding speculative risk-taking deep within everyday life. Our article first notes some of the resonances in the ways that cryptocurrency exchanges and gambling markets are organized. We also indicate that cryptocurrency exchange—like gambling—draws some of its appeal from a backdrop of uncertainty and vast inequity in contemporary capitalism. Then, taking advantage of the ‘analytic multiplier effects’ that come from holding the concepts of financialization and gamblification together, we work to decrypt some of the obfuscating elements of cryptocurrency discourse.